1982
DOI: 10.1177/036354658201000303
|View full text |Cite
|
Sign up to set email alerts
|

Injuries in Intercollegiate Wrestling

Abstract: A 5-year study of the injuries sustained by a single intercollegiate wrestling team is presented. The total number of injuries, a description of the injuries classified according to anatomical distribution, and mechanism of injury are given. A high incidence of upper body injuries is noted, and comments are made concerning protective measures that can be taken.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 8 publications
1
28
1
Order By: Relevance
“…The difficulty in the comparison of data among studies is due to the absence of an uniform standard in the classification of lesion types. 4 The types of lesion most frequently reported in our study were sprains (34.5%) and muscle lesions (30.4%), which is in line with the results presented by Jarrett et al 4 , Pasque et al 5 and Snook 6 . These authors said that contusions are the third most common lesion in wrestlers, unlike our data in which contusions were the least frequent lesions.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The difficulty in the comparison of data among studies is due to the absence of an uniform standard in the classification of lesion types. 4 The types of lesion most frequently reported in our study were sprains (34.5%) and muscle lesions (30.4%), which is in line with the results presented by Jarrett et al 4 , Pasque et al 5 and Snook 6 . These authors said that contusions are the third most common lesion in wrestlers, unlike our data in which contusions were the least frequent lesions.…”
Section: Discussionsupporting
confidence: 92%
“…In a similar manner, Jarrett et al 4 said that 6% of the lesions required surgical treatment and Agel et al 1 and Wroble et al 14 reported that most of the lesions that required surgical treatment occurred in the knee. Several authors [4][5][6]12,15 , using different methods to evaluate severity, report that the majority of traumatisms in wrestlers are not considered severe. In our study, the average length of absence from sport due to injury was 2.1 months.…”
Section: Lower Limbs Upper Limbs Trunkmentioning
confidence: 99%
“…There have been studies following individual collegiate teams for several seasons. 6,7 Others have reviewed injuries of age groups other than college, or injuries occurring during specific competitions or training camps. [1][2][3][4] There are no previous studies involving many institutions over a long period of time, which would decrease the chance that a single year with an unusually high number of injuries would influence the results.…”
mentioning
confidence: 99%
“…Neck injuries frequently occur in such contact sports as wrestling, American football, rugby, judo and sumo (Estwanik et al 1978(Estwanik et al , 1980Roy 1979;Snook 1982;Albright et al 1985;Torg et al 1985;Wu and Lewis 1985;Wroble and Albright 1986;Katoh et al 1996;Jarrett et al 1998;Wetzler et al 1998). Regular physical examination and increasing the neck muscle strength has been reported to play an important role in preventing such injuries in contact sports (Chrisman et al 1965;Maroon et al 1977;Diange 1984;Brzycki 1985;Vegso et al 1987;Beachy et al 1997;Tsuyama et al 1999).…”
Section: Introductionmentioning
confidence: 99%